Effect of different solvent in the preparation of polyethersulfone(pes)-ag polymer composite - Basri, Hatijah; Ismail, Ahmad Fauzi; Aziz, Madzlan (Penerbit UTM Press, 2008)
Organic-inorganic composite materials have attracted great attention because of their potential to combine the features of organic materials with those of inorganic materials. Particularly organic-metal composite such as polymer-silver are promising functional materials in areas ranging from electronic and optical devices to biosensing, antimicrobial agents and catalysis. In general, there are two synthetic approaches of silver-polymer nanostructures : in situ and ex situ methods. In this study silver-polyethersulfone (PES) was prepared in situ. The morphology of the samples which has undergone permeation measurement was characterized by Field Emission-Scanning Electron Microscopy (FE-SEM)/Energy Dispersive X-Ray Analysis (EDX). The differences in their structure arises from using different solvents N-Methyl-2-pyrrolidone (NMP) which was labeled A16 and N,N-dimethylformamide (DMF) which was labeled B16. Fingerlike structure was observed for B16 while mixed finger-like and spongy structure with voids was observed for A16. Pure water permeability measurement proved that B16 can permeate five times better than A16. However, rejection by membranes only differs by 7.3%. Hence, the performance of composite can be explained in terms of the observed surface and cross section micrographs, which in turn is correlated with the permeation measurement.